Pengaruh Jenis Kemasan Terhadap Karakteristik Cookies Ampas Tahu Selama Penyimpanan - Risma Dewi, Putu; Trisna Darmayanti, Luh Putu; Nocianitri, Komang Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 2 (2022): Jurnal ITEPA, 2022)
This study aims to determine the effect of the type of packaging on tofu dregs cookies during storage and the best type of packaging alarm that can maintain the balance of tofu dregs cookies during storage. The experimental design used was factorial Completely Randomized Design (CRD) with 2 factors. The first factor was the type of packaging with 3 levels, namely K1 = Polypropylene, K2 = Polyethylene, K3 = Aluminum Foil. The second factor, namely storage time with 5 stages, namely P0 = 0 weeks, P1 = 1 week, P2 = 2 weeks, P3 = 3 weeks, and P4 = 4 weeks. The treatment was repeated 2 times in order to obtain 30 experimental units. The data obtained were analyzed using Analysis of Variance (ANOVA). If the influence affects the test parameters, then test with Duncan's Multiple Range Test. The type of packaging during storage affects water content, texture, crude fiber content, TBA number, hedonic test (aroma, texture, color, taste and overall acceptance). This type of aluminum foil packaging can maintain the characteristics of tofu dregs cookies for up to 3 weeks with the following characteristics: moisture content of 3.73%, texture 51.90 N, crude fiber content 4.20%, TBA number 0.32 mg malonaldehyde / kg, for preference tests such as color, aroma, texture, taste and overall acceptance is preferred.